The optimal use of automated office blood pressure measurement in clinical practice - Andreadis, Emmanuel A. (J Clin Hypertens (Greenwich), 2020)
This evidence‐based article endorses the use of automated office blood pressure (AOBP). AOBP is the most favorable office blood pressure (BP) measuring technique as it provides accurate readings with 3‐15 mm Hg lower values than the casual conventional office measurements with auscultatory or semi‐automated oscillometric devices and relates closely to awake ABP readings. The AOBP technique seems to be superior to conventional office BP in predicting hypertension‐mediated organ damage and appears to be equally reliable to awake ABP in the prediction of cardiovascular (CV) disease. AOBP readings should be obtained either unattended, with the patient alone in the examination room, or attended with the presence of personnel in the room but with no talking to the patient, although this recommendation is not frequently followed in routine clinical practice. To optimize office BP readings, the type of device, the rest period before AOBP measurements (preceding rest), and the time intervals between measurements were evaluated. As AOBP readings have the advantage of removing many confounding factors, the authors propose to perform measurements with a preceding rest in all patients at the initial visit; if AOBP readings remain <130 mm Hg in subsequent visits, measurements could be accepted, otherwise, if are higher, patients should be evaluated by out‐of‐office BP measurements.